The delayed effect of wildfire season particulate matter on subsequent influenza season in a mountain west region of the USA. (June 2020) - Landguth, Erin L.; Holden, Zachary A.; Graham, Jonathan; Stark, Benjamin; Mokhtari, Elham Bayat; Kaleczyc, Emily; Anderson, Stacey; Urbanski, Shawn; Jolly, Matt; Semmens, Erin O.; Warren, Dyer A.; Swanson, Alan; et al.
Highlights: Prior studies of wildfire smoke have focused on acute cardiopulmonary health effects. Novel analysis of wildfire season particulate matter and influenza occurrence months later. Air pollution during wildfire seasons associated with influenza months later. Air pollution during winter period not associated with influenza days later. Abstract: Particularly in rural settings, there has been little research regarding the health impacts of fine particulate matter (PM2.5 ) during the wildfire season smoke exposure period on respiratory diseases, such as influenza, and their associated outbreaks months later. We examined the delayed effects of PM2.5 concentrations for the short-lag (1–4 weeks prior) and the long-lag (during the prior wildfire season months) on the following winter influenza season in Montana, a mountainous state in the western United States. We created gridded maps of surface PM2.5 for the state of Montana from 2009 to 2018 using spatial regression models fit with station observations and Moderate Resolution Imaging Spectroradiometer (MODIS) aerosol optical thickness data. We used a seasonal quasi-Poisson model with generalized estimating equations to estimate weekly, county-specific, influenza counts for Montana, associated with delayed PM2.5 concentration periods (short-lag and long-lag effects), adjusted for temperature and seasonal trend. We did not detect an acute, short-lag PM2.5 effect nor short-lag temperature effect on influenza in Montana. Higher daily average PM2.5 concentrations during the wildfire season was positively associated with increased influenza in the following winter influenza season (expected 16% or 22% increase in influenza rate per 1 μg/m 3 increase in average daily summer PM2.5 based on two analyses, p = 0.04 or 0.008). This is one of the first observations of a relationship between PM2.5 during wildfire season and influenza months later.